2020
DOI: 10.15403/jgld-2623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Association between Programmed Cell Death-1 Gene Polymorphisms and Hepatocellular Carcinoma Susceptibility in Turkish Subjects. A Pilot Study

Abstract: Background and Aims: Programmed cell death-1 (PD-1) has a vital role in regulating T-cell function, and immune escape mechanism of cancer cells. It was shown that there could be a relationship between single nucleotide polymorphisms (SNPs) in the PD-1 gene and susceptibility to hepatocellular carcinoma (HCC) based on various studies. We aimed to investigate the role of three SNPs within the PD-1 gene in susceptibility to HCC in the Turkish population. Methods: Single nucleotide polymorphisms of PD-1.1, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…A study performed in 2015 also found no significant differences in the genotype distributions of PD-1 rs11568821 and rs41386439 in chronic HBV patients compared to the spontaneously recovered control group[ 138 ], indicating the possibility of lack of association between PD-1 gene polymorphisms and HBV infection susceptibility and HBV-related HCC progression in Turkish patients. These findings were confirmed in a more recent study investigating three PD-1 gene polymorphisms and HCC progression; again no significant distribution of rs36084323, rs2227981, and rs10204525 genotypes were observed in HCC cases in Turkish patients[ 139 ].…”
Section: Pd-1/pd-l1 Genetic Variationssupporting
confidence: 67%
“…A study performed in 2015 also found no significant differences in the genotype distributions of PD-1 rs11568821 and rs41386439 in chronic HBV patients compared to the spontaneously recovered control group[ 138 ], indicating the possibility of lack of association between PD-1 gene polymorphisms and HBV infection susceptibility and HBV-related HCC progression in Turkish patients. These findings were confirmed in a more recent study investigating three PD-1 gene polymorphisms and HCC progression; again no significant distribution of rs36084323, rs2227981, and rs10204525 genotypes were observed in HCC cases in Turkish patients[ 139 ].…”
Section: Pd-1/pd-l1 Genetic Variationssupporting
confidence: 67%
“…Another research has previously reported PDCD-1 rs10204525 C > T SNP acquired significance after adjusting for other risks, being most notable in the smaller numbers of women with NAFLD-HCC in Caucasian patients [ 22 ]. Contrary to these studies, the rs10204525 SNP was found to have an insignificant role in patients with HCV-related hepatic disorders (chronic infection, cirrhosis, and HCC) in the Italian cohort [ 23 ] and was not a predisposing factor for HCC development in the Turkish population [ 11 ]. In the present study, our results also demonstrated no association between rs10204525 T > C and HCC risk, which was consistent with De Re V’s study in the Italian cohort and Demirci AF’s study in the Turkish population [ 11 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these studies, the rs10204525 SNP was found to have an insignificant role in patients with HCV-related hepatic disorders (chronic infection, cirrhosis, and HCC) in the Italian cohort [ 23 ] and was not a predisposing factor for HCC development in the Turkish population [ 11 ]. In the present study, our results also demonstrated no association between rs10204525 T > C and HCC risk, which was consistent with De Re V’s study in the Italian cohort and Demirci AF’s study in the Turkish population [ 11 , 23 ]. Although the allele distribution of the PDCD-1 rs10204525 genotype in the control group in this study was not similar to the distribution of the previously studied Northwest China and other population, it had no differences with the distribution of CDX and KHV populations ( http://asia.ensembl.org/Homo_sapiens/Variation/Population?db=core;v=rs10204525;vdb=variation , P = 0.89 and P = 0.78, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations